International migration and income inequality - Nicola Coniglio; Vitorocco Peragine; Davide Vurchio (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2023)
In this paper we explore the links between international migration and income inequality. After presenting a simple model which considers the role of income distribution in individual decisions to migrate, we estimate a set of models on the determinants of yearly bilateral migration from a very large pool of countries in the period 1960-2019. The empirical results confirm that inequality-in both origin and destination countries-significantly shapes individual choices about where, and whether, to migrate. We find that the effect of inequality at both ends of migration corridors is heterogeneous across countries at different levels of development, most likely due to differences in migration barriers and in the patterns of migrants' self-selection. In the second part of the study, we explore the direct effect of international migration on global inequality, by assessing how the current level of migration in the world has likely affected income inequality between and within nations. By adopting a counterfactual methodology, we find that migration flows lead to lower between-country inequality and higher within-country inequality, compared with a scenario with no migration. The overall impact is a negligible reduction in global inequality. The impact of migration on inequality, although small, tends to increase over time.
Keywords: F22; I3; D63; 330; international migration; inequality; income distribution